2005
DOI: 10.1590/s1516-635x2005000300002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of free-choice feeding on the performance and ileal digestibility of nutrients in broilers

Abstract: An experiment was conducted to study ileal digestibility of nutrients and to verify the ability of broilers to select feed in order to meet their requirements for protein and energy. The treatments consisted of six diets: R+S: free-choice feeding with rice bran (energy) and soybean meal (protein); C+G: free-choice feeding with corn (energy) and corn gluten meal (protein); R+G: free-choice feeding with rice bran (energy) and corn gluten meal (protein); C+S: free-choice feeding with corn (energy) and soybean mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…Moreover, exposing animals to extreme treatments only (i.e., mixed ration vs. freechoice among ingredients) may not clearly express their ability to select a balanced diet when daily fluctuations in food consumptions are high, as it was observed in T100:0 in the present study. Conversely, our results do agree with studies with broilers which revealed that, when animals were exposed to choice feeding among ingredients, protein intake was lower than expected, thus leading to lower performance (Siegel et al, 1997;Yo et al, 1998;Cruz et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, exposing animals to extreme treatments only (i.e., mixed ration vs. freechoice among ingredients) may not clearly express their ability to select a balanced diet when daily fluctuations in food consumptions are high, as it was observed in T100:0 in the present study. Conversely, our results do agree with studies with broilers which revealed that, when animals were exposed to choice feeding among ingredients, protein intake was lower than expected, thus leading to lower performance (Siegel et al, 1997;Yo et al, 1998;Cruz et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Along the days, birds instigated by their active and curious behavior were able to self-select other components to promote regular growth. Interestingly, the most consumed component reverted to be TM meal (protein-and energy-rich), followed by ground corn (energy content), which indicates the capability of birds to regulate the consumption of ingredients to maintain the energy: protein ratio according to their nutritional needs [40]. Moreover, the unquestionable shift from a conventional protein source (soybean) to TM meal was observed and it may demonstrate that birds opted to feed on TM meal because of its sensory characteristics as well as good nutritional profile.…”
Section: Discussionmentioning
confidence: 99%
“…Since as the percentage of inclusion increased, feed intake decreased significantly, the nutrient and energy intake increased, and therefore caused greater satiety in birds, although it could be due to the fiber effect discussed above and not by what they claim. In this respect, Aami-Azghadi et al (2014) and Cruz et al (2005) suggest that diets should contain protein and energy densities according to the stage of development of the birds. In the diets used in this study, the protein level was constant and the energy, raw fiber and dietary fiber increased with the greater inclusion of MOR (Table 1).…”
Section: Inclusion Of Moringa Leaf Powder (Moringa Oleifera) In Foddementioning
confidence: 99%